Artificial intelligence as an enabler for achieving human resource resiliency: past literature, present debate and future research directions - Gayatri Panda; Manoj Kumar Dash; Ashutosh Samadhiya; Anil Kumar; Eyob Mulat-weldemeskel (International Journal of Industrial Engineering and Operations Management)
Purpose – Artificial intelligence (AI) can enhance human resource resiliency (HRR) by providing the insights and resources needed to adapt to unexpected changes and disruptions. Therefore, the present research attempts to develop a framework for future researchers to gain insights into the actions of AI to enable HRR. Design/methodology/approach – The present study used a systematic literature review, bibliometric analysis, and network analysis followed by content analysis. In doing so, we reviewed the literature to explore the present state of research in AI and HRR. A total of 98 articles were included, extracted from the Scopus database in the selected field of research. Findings – The authors found that AI or AI-associated techniques help deliver various HRR-oriented outcomes, such as enhancing employee competency, performance management and risk management; enhancing leadership competencies and employee well-being measures; and developing effective compensation and reward management. Research limitations/implications – The present research has certain implications, such as increasing the HR team's proficiency, addressing the problem of job loss and how to fix it, improving working conditions and improving decision-making in HR. Originality/value – The present research explores the role of AI in HRR following the COVID-19 pandemic, which has not been explored extensively.